Disruptions of frontostriatal language functions in Parkinson’s disease - García, Adolfo M.; Bocanegra, Yamile; Birba, Agustina; Orozco-Arroyave, Juan Rafael; Sedeño, Lucas; Ibáñez, Agustín (Elsevier, 2020)
Atrophy of frontostriatal pathways in Parkinson’s disease compromises diverse linguistic functions. To establish which of these disorders constitute candidate cognitive biomarkers of the disease, we review studies assessing phonetic/phonological, morphological, lexicosemantic, syntactic, and discourse-level dimensions in early stage patients. While morphological difficulties are inconsistent and discourse-level alterations seem nosologically unspecific, systematic disturbances emerge in particular phonetic (plosive articulation), lexicosemantic (action-verb processing), and syntactic (complex-sentence parsing) functions. Some such deficits are selective (not generalized across their overarching domain), partially specific (absent in nonmotor disorders), primary (not secondary to overall cognitive dysfunction), associated with critical neurobiological abnormalities, and traceable in prodromal stages. Notably, new approaches for analyzing those dimensions allow identifying individual patients with over 90% accuracy. Although several challenges remain unaddressed and more programmatic research is needed, the incorporation of these tools in clinical settings could enhance screening protocols, differential diagnosis, disease-progression monitoring, and discrimination of patient profiles within the parkinsonian population.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Cognitive biomarkers; Discourse-level processing; Frontostriatal pathways; Lexicosemantics; Morphology; Neurolinguistics; Parkinson’s disease; Phonetics/phonology; Syntax